Characteristics of Straight Trapezoidal Cross-Sectional Fins under Unsteady Conditions - Seen, Michael; Purwadianto, Doddy; Dyaksa, Gilang Argya; Winarbawa, Heryoga; Rines, Rines; Mardikus, Stefan; Kusbandono, Wibowo; Lukiyanto, Y. B. (International Journal of Applied Sciences and Smart Technologies, 2024)
The aim of this research is to understand the characteristics of fins with a trapezoidal cross-section. The shape of the fin's cross-section is one of the influential factors affecting fin characteristics. In the design of fins, it is crucial to comprehend the characteristics of the fin as they relate to temperature distribution, heat transfer rate, and the efficiency of the fin. The research was conducted using numerical computation with an explicit finite difference method. Variations were made in the length of side 3 of the trapezium to 0 m, 0.02 m, and 0.04 m. The research results indicate that increasing the width of the fin enhances the temperature distribution, flow rate, and efficiency achievable by the fin. Significant improvement occurred when varying the side length from 0 m to 0.02 m, whereas subsequent variations did not considerably alter the efficiency. The highest efficiency achieved was 0.90 when the length of side 3 was 4 cm at the 300 seconds.